1177 B.C. : a graphic history of the year civilization collapsed - Cline, Eric H. (Turning points in ancient history., 2024)
"A beautiful, full-color graphic version of Eric Cline's bestselling 1177 B.C., adapted by award-winning author-illustrator Glynnis FawkesEric Cline's 1177 B.C. tells the story of one of history's greatest mysteries: what caused the ancient civilizations of the Aegean and Eastern Mediterranean to collapse more than three thousand years ago, bringing the Late Bronze Age to an abrupt end? In this vivid and captivating full-color graphic adaptation of the landmark book, author-illustrator Glynnis Fawkes invites us to follow two young friends living in the aftermath of the cataclysm as they unravel why it happened-and reveal important lessons for today's interconnected and vulnerable world.Pel, a member of the marauding Sea Peoples, and Shesha, an Egyptian scribe, visit the kingdoms of the Minoans, Mycenaeans, Hittites, Canaanites, Assyrians, and Egyptians to explore the calamities that brought them down. This graphic history depicts the people, events, art, architecture, and lands that Pel and Shesha encounter. We witness the Sea Peoples' battles on land and sea, earthquakes on the Greek mainland, droughts and famine in Anatolia, invasions in north Syria, and possible rebellions in Canaan. Along the way, we also learn about the assassination of a Hittite prince traveling to marry an Egyptian queen, the sinking of a merchant ship laden with international goods, and the return of a pair of sandals to Crete by the Babylonian king Hammurabi.An entertaining adventure story, this dazzling comic is also historically accurate and enlightening, inviting readers of all ages to think about the surprising factors and theories that explain why societies, whether ancient or modern, die or survive when struck by catastrophes"--